The first fatal case of Yam bean and Rotenone toxicity in Thailand - Narongchai P. (2014)
The first fatal case of Yam bean and Rotenone toxicity in Thailand was studied at Forensic Medicine, Chiang Mai, Thailand. A Chinese Taiwan man, 59 years old, was found dead after Yam bean ingestion. Yam bean toxicity and death have been found very rarely in the world and has not been reported in Thailand. The Yam bean plant is grown widely in Northern Thailand. But many people know that mature pods, seeds and filage of the Yam bean, except the tuberous root, are very toxic. The victim ate a lot of Yam bean seeds and died within 2 hours with respiratory failure. The authors detected Rotenone substance in Yam bean seeds, gastric content and 72 ng/ml blood by HPLC. Also generalized microscopic hemorrhage in the brain, lungs, liver and adrenal glands which were of characteristic pathology were detected. The authors concluded that the cause of death was asphyxia from Yam bean or Rotenone toxicity.